Seroprevalence of Hepatitis B Virus (HBV) among Blood donors in Federal Medical Centre Nguru, Yobe State, Nigeria (Journal of Environmental Bioremediation and Toxicology, 2023)
The hepatitis B virus is responsible for a highly contagious infectious disease that is transmitted through contact with infected blood or body fluids to non-immune persons, transfusion of blood containing infections, engaging in close, intimate sexual interactions, sharing of contaminated sharp objects, close personal contact in overcrowded environments, and via the placenta of an infected mother to an unborn child. This work aims to determine the seroprevalence of hepatitis B virus among blood donors in Federal Medical Centre Nguru, Yobe State, Nigeria. The screening of HBsAg was carried out using the BioApex one Step HBsAg test kit manufactured by Richmond Hill, Ontario, Canada. Nine (9) out of one hundred persons screened for HBsAg tested positive, giving a seroprevalence of 9.0%. Seroprevalence was significantly higher in donors of the age group 35–44 years old compared to donors of other age groups. The highest prevalence of 11.1% was recorded in donors with tertiary education. Fifty-three percent (53%) of the sample population did not have any knowledge about HBV prior to this study and had the highest prevalence of 6(11.3%) with P
Keywords: Hepatitis B; Blood donors; Seroprevalence; HBsAg screening; Awareness campaigns